Catalytic behavior of La–Sr–Ce–Fe–O mixed oxidic/perovskitic systems for the NO+CO and NO+CH4+O2 (lean-NOx) reactions - Belessi, Vassiliki; Costa, Costas; Bakas, Thomas V.; Anastasiadou, T.; Pomonis, Phillippos J.; Efstathiou, A. M. (My University, 2000)
Mixed oxides of the general formula La0.5SrxCeyFeOz were prepared by using the nitrate method and characterized by XRD and Mössbauer techniques. The crystal phases detected were perovskites LaFeO3 and SrFeO3−x and oxides α-Fe2O3 and CeO2 depending on x and y values. The low surface area ceramic materials have been tested for the NO+CO and NO+CH4+O2 (“lean-NOx”) reactions in the temperature range 250–550°C. A noticeable enhancement in NO conversion was achieved by the substitution of La3+ cation at A-site with divalent Sr+2 and tetravalent Ce+4 cations. Comparison of the activity of the present and other perovskite-type materials has pointed out that the ability of the La0.5SrxCeyFeOz materials to reduce NO by CO or by CH4 under “lean-NOx” conditions is very satisfying. In particular, for the NO+CO reaction estimation of turnover frequencies (TOFs, s−1) at 300°C (based on NO chemisorption) revealed values comparable to Rh/α-Al2O3 catalyst. This is an important result considering the current tendency for replacing the very active but expensive Rh and Pt metals. It was found that there is a direct correlation between the percentage of crystal phases containing iron in La0.5SrxCeyFeOz solids and their catalytic activity. O2 TPD (temperature-programmed desorption) and NO TPD studies confirmed that the catalytic activity for both tested reactions is related to the defect positions in the lattice of the catalysts (e.g., oxygen vacancies, cationic defects). Additionally, a remarkable oscillatory behavior during O2 TPD studies was observed for the La0.5Sr0.2Ce0.3FeOz and La0.5Sr0.5FeOz solids.
Keywords: Perovskites; NO reduction; Lean-NOx; O2 TPD; NO TPD; Oscillations